Genetic bases related to the development of non-syndromic dental agenesis: a literature review (Research, Society and Development, 2020)
Non-syndromic dental agenesis is characterized as the most common developmental anomaly in humans, causing the lack of one or more teeth, in deciduous or permanent dentition. Mutations in specific genes of dental development are pointed as etiological factors of this anomaly. To perform this work, two electronic databases were consulted to conduct a literature survey, including PubMed and BVS. The descriptor "Anodontia" was used in both. The articles were filtered from 2010 to 2020, including full texts, in english, portuguese and spanish. Dissertations, theses and book chapters were discarded. In PubMed, from 508 articles found, 13 were included for review. In the BVS, from 304 articles found, 07 were included for review, totaling 20 articles. Studies have shown that mutations by nucleotide subitusing and deletion were more present in genes that cause dental agenesis (PAX9, MSX1, AXIN2, WNT). In epidemiologic studies, women showed greater involvement than men, both in deciduous and permanent dentition, in a ratio of 3:2. In addition, leukoderms showed greater involvement than melanoderms. Knowledge of the genotype-phenotype correlation between mutations and dental agenesis is important for the dental surgeon, as it assists in diagnosis, genetic counseling, treatment and prognosis.